Bauhaus-Paradigmen Künste, Design und Pädagogik - Röhl, Anne 1984-; Schütte, André 1985-; Knobloch, Phillip D. Th. 1976-; Hornäk, Sara 1971-; Henning, Susanne 1967-; Gimbel, Katharina (De Gruyter, 2021)
As a result of its aspiration to design the world comprehensively and to take action pedagogically based on the arts, the Bauhaus established an inseparable link between architecture, design, art, and pedagogy. The effects of this in-depth desire for reform can also still be recognized in art, architecture, design, and contemporary processes of aesthetic education one hundred years after the school's founding. The resonance of the Bauhaus is thus the topic of this book. Thevarious texts reflect on the Bauhaus from the perspectives of the history of art and design, art education, and educational science with respect to the aspects: reception in popular culture, education through design, material in teaching, and the Bauhaus as a regulative idea in the digital age
Keywords: Staatliches Bauhaus; Geschichte; Design; Künste; Rezeption; Massenkultur; Bauhaus; Kunsterziehung; Aufsatzsammlung